2022
DOI: 10.3390/life12030463
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mGlu5 Receptor Signaling Are Associated with Associative Learning and Memory Extinction in Mice

Abstract: Using an in vivo method for the assessment of polyphosphoinositide (PI) hydrolysis, we examine whether spatial learning and memory extinction cause changes in mGlu5 metabotropic glutamate receptor signaling in the hippocampus and prefrontal cortex. We use the following five groups of mice: (i) naive mice; (ii) control mice exposed to the same environment as learner mice; (iii) leaner mice, trained for four days in a water maze; (iv) mice in which memory extinction was induced by six trials without the platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Differential activation of these pathways by different ligands has been previously observed in group 1 mGlu receptors and the therapeutic consequences of this must be considered [ 93 , 94 ]. mGlu5 receptor signalling bias has also been linked to particular cognitive effects, with spontaneous memory loss associated with PFC mGlu5 receptor signalling bias towards a PI-independent pathway [ 95 ]. Here, we show that the effects of both VU0409551 and VU0360172 are at least partly mediated by PLC activation, which induces downstream calcium mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Differential activation of these pathways by different ligands has been previously observed in group 1 mGlu receptors and the therapeutic consequences of this must be considered [ 93 , 94 ]. mGlu5 receptor signalling bias has also been linked to particular cognitive effects, with spontaneous memory loss associated with PFC mGlu5 receptor signalling bias towards a PI-independent pathway [ 95 ]. Here, we show that the effects of both VU0409551 and VU0360172 are at least partly mediated by PLC activation, which induces downstream calcium mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, our study indicated that VC might be associated with alterations in the phosphoinositide (PI) and p-ERK1/2 pathways mediated by mGluR1α. Teleuca et al 32 utilized in vivo techniques to evaluate PI levels and investigated potential impairments in spatial learning and memory. Their primary objective was to examine the influence of changes in mGluR1 signaling on the PI pathway, as well as the MAP kinase and phosphatidylinositol-3-kinase pathways, in the hippocampus and prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Metabotropic glutamate (mGlu) receptors comprise a family of G-protein coupled receptors that are present throughout the brain [ 1 , 2 ] and are highly expressed in the hippocampus [ 2 ]. They are specifically involved in the regulation of persistent (>24 h) forms of hippocampal synaptic plasticity, such as long-term potentiation (LTP) and long-term depression (LTD) [ 3 , 4 , 5 , 6 , 7 , 8 ], hippocampus-dependent learning [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].They also support hippocampal information transfer by means of neuronal oscillations [ 16 , 17 ] and the beneficial effects of environmental enrichment on hippocampal function [ 18 ].…”
Section: Introductionmentioning
confidence: 99%